Study on support for HALF beam position monitor displacement measurement system. (September 2022) - Wang, Chuhan; Lan, Jinkai; Luo, Qing; Wang, Anxin; Zhou, Tianyu; Sun, Baogen
Hefei Advanced Light Facility (HALF), is a fourth-generation vacuum ultraviolet and X-ray diffraction limit synchrotron radiation (DLSR) light source under preliminary research and construction. Beam position monitor (BPM) displacement measurement system with nanometer resolution is used to correct the BPM data and achieve sub-micron beam orbit stability. In order to make full use of the performance and meet the requirement of HALF's beam orbit stability, the supports of the system are particularly crucial. The purpose of this paper is to develop a set of support for the BPM displacement system that meet the stability requirements of HALF. A hybrid support with Invar 36 and carbon fiber/epoxy is creatively proposed to achieve stability requirements. Through the calculation of thermal expansion, the analysis of mechanical vibration and finite element analysis (FEA), the hybrid support is adjusted to higher stability. Experiments are conducted and show that the hybrid support has higher stability than traditional support. On the existing experimental platform, the vibration RMS of the hybrid support was measured at 42.6 nm in horizontal and 29.9 nm in vertical and the hybrid support could meet the requirement of HALF's beam orbit stability.